Novel Markers in Pediatric Acute Lymphoid Leukemia: The Role of ADAM6 in B Cell Leukemia - Alsuwaidi, Laila; Hachim, Mahmood; Senok, Abiola (Frontiers in Cell and Developmental Biology, 2021)
Background The extensive genetic heterogeneity found in the B cell precursor acute lymphoblastic leukemia (BCP-ALL) subtype of childhood ALL represents a potential repository of biomarkers. To explore this potential, we have carried out in silico analysis of publicly available ALL datasets to identify genetic biomarkers for childhood BCP-ALL, which could be used either individually or in combination as markers for early detection, risk stratification, and prognosis. Methods To explore novel genes that show promising clinical and molecular signatures, we examined the cBioPortal online tool for publicly available datasets on lymphoid cancers. Three studies on lymphoblastic and lymphoid leukemia with 1706 patients and 2144 samples of which were identified. Only B-Lymphoblastic Leukemia/Lymphoma samples (n = 1978) were selected for further analysis. Chromosomal changes were assessed to determine novel genomic loci to analyze clinical and molecular profiles for the leukemia of lymphoid origin using cBioPortal tool. Results ADAM6 gene homozygous deletions (HOM:DEL) were present in 59.60% of the profiled patients and were associated with poor ten years of overall patients’ survival. Moreover, patients with ADAM6 HOM:DEL showed a distinguished clinical and molecular profile with higher Central Nervous System (CNS) sites of relapse. In addition, ADAM6 HOM:DEL was significantly associated with unique microRNAs gene expression patterns. Conclusion ADAM6 has the potential to be a novel biomarker for the development and progress of BCP- ALL.